2006
DOI: 10.1191/1358863x06vm662oa
|View full text |Cite
|
Sign up to set email alerts
|

Markers of vascular inflammation are associated with the extent of atherosclerosis assessed as angiographic score and treadmill walking distances in patients with peripheral arterial occlusive disease

Abstract: The importance of inflammation in atherosclerosis is well established in cardiovascular disease. However, limited data exist on the relationship between vascular inflammation and the severity of peripheral arterial occlusive disease (PAD). We investigated the relationship between biochemical markers of vascular inflammation and the diagnostic measures of PAD: ankle-brachial pressure index (ABI), maximum treadmill walking distance and angiographic score. In 127 patients (mean age 66 years; 64% males) with angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 46 publications
2
52
0
3
Order By: Relevance
“…After adjusting for potential confounders, including baseline albuminuria tors, including smoking, hyperlipidemia, hypertension, diabetes and chronic inflammation, may contribute to the presence of both albuminuria and low ABI 19,20) . Secondly, it has been suggested that albuminuria is a marker of endothelial dysfunction 21,22) .…”
Section: Resultsmentioning
confidence: 99%
“…After adjusting for potential confounders, including baseline albuminuria tors, including smoking, hyperlipidemia, hypertension, diabetes and chronic inflammation, may contribute to the presence of both albuminuria and low ABI 19,20) . Secondly, it has been suggested that albuminuria is a marker of endothelial dysfunction 21,22) .…”
Section: Resultsmentioning
confidence: 99%
“…Markers of vascular inflammation relate to lower functional measures in PAD patients. 109, 110 Higher peripheral monocyte expression of tumor necrosis factor α is associated with lower treadmill walking time in patients with intermittent claudication. 111 In a similar fashion, higher peripheral mononuclear expression of the pro-inflammatory mediator, Wnt5a, is associated with lower ABI.…”
Section: Skeletal Muscle Alterations and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Severity of stenosis was assessed according to the following validated grading system: 0 ¼ normal; 1 ¼ stenosis o50%; 2 ¼ stenosis 450%; 3 ¼ occlusion. 13 Different scores for each of the 21 segments were then added up to obtain an angiographic score for each patient, 63 being the maximal score. The angiographic score was evaluated independently by an experienced radiologist, who was blinded to the results of hemodynamic and laboratory measurements.…”
Section: Angiographic Scorementioning
confidence: 99%
“…11 Angiographic score (ASc) assessed by digital subtraction angiography provides information about distribution and severity of atherosclerotic lesions in the arteries of the lower extremities. 12 The ASc is inversely related to ankle-brachial pressure index (ABPI) and maximum walking distance, 13 and is positively associated with biomarkers of inflammation 13 and oxidative stress 14 in patients with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%